2003
DOI: 10.1381/096089203322509228
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep-Related Breathing Disorders in Patients Evaluated for Bariatric Surgery

Abstract: This population of clinically severe obese patients being evaluated for bariatric surgery had an 88% incidence of an OSRBD, 71% with OSA. Appropriate therapy with CPAP perioperatively would theoretically prevent hypoxic complications associated with OSRBD. Providers should have a low threshold for ordering a PSG as part of the preoperative evaluation for bariatric surgery. Empiric CPAP at 10 cm H2O should be considered for those patients who cannot complete a PSG before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
1
15

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(176 citation statements)
references
References 15 publications
10
150
1
15
Order By: Relevance
“…We demonstrated a greater than 80% prevalence of OSA in severe obesity, which is consistent with previous reports (10,11,36). Thus, in severe obesity metabolic dysfunction can be related not only to adiposity per se but also to concomitant OSA.…”
Section: Osa Systemic Inflammation and Metabolic Dysfunction In Sevsupporting
confidence: 93%
See 1 more Smart Citation
“…We demonstrated a greater than 80% prevalence of OSA in severe obesity, which is consistent with previous reports (10,11,36). Thus, in severe obesity metabolic dysfunction can be related not only to adiposity per se but also to concomitant OSA.…”
Section: Osa Systemic Inflammation and Metabolic Dysfunction In Sevsupporting
confidence: 93%
“…Both insulin resistance and systemic inflammation may contribute to the increased cardiovascular risk in patients with OSA (7)(8)(9). Insulin resistance, systemic inflammation, and OSA are particularly prevalent in patients with severe obesity defined as a body mass index (BMI) exceeding 40 kg/m 2 (2,(10)(11)(12). While obesity causes systemic inflammation, insulin resistance, and sleep apnea (12)(13)(14)(15), sleep apnea may further exacerbate the inflammatory and metabolic disturbances (2,3,6).…”
mentioning
confidence: 99%
“…However, our data are much lower than those found in previous studies, in which obese patients were submitted to polysomnography and was found a prevalence of OSAHS in 83.7% and 71% of the patients (12,22) . Other study identified mild sleep disturbance in 21.9% of obese patients, moderate in 28.8% and severe in 49.3% (23) .…”
Section: Discussioncontrasting
confidence: 91%
“…In severe obesity (BMI . 40 kg/m 2 ), the prevalence of sleep apnea was estimated to vary between 40 and 90% (17)(18)(19)(20)(21)(22)(23)(24), and the severity of sleep apnea was generally greater than that found in leaner clinical populations (17,25,26). In addition, Peppard and colleagues have provided further evidence for a link between sleep apnea and obesity by demonstrating that a 10% change in body weight was associated with a parallel change of approximately 30% in the apnea-hypopnea index (AHI), the major index of sleep apnea severity (16).…”
Section: Sleep Apnea Risk Factors: Roles Of Obesity Sex Fat Distribmentioning
confidence: 99%